Effects of Dietary Levels of Calcium and Nonphytate Phosphorus in Broiler Starter Diets on Live Performance, Bone Development and Growth Plate Conditions in Male Chicks Fed a Corn-Based Diet - Coto, Cesar; Yan, F.; Cerrate, S.; Wang, Z.; Sacakli, P.; Halley, J.T.; Wiernusz, C.J.; Martinez, A.; Waldroup, P.W. (International Journal of Poultry Science, 2008)
A study was conducted to evaluate the effects of dietary levels of calcium (Ca), nonphytate P (NPP), phytase (Phy) and 25-hydroxycholecalciferol (25-OH) on live performance and bone development in male chicks fed a corn-based diet. Dietary treatments consisted of a 2×2×4×4 factorial arrangements with two levels of supplemental phytase (0 or 1200 FTU kg-1), two levels of 25-OH (0 or 69 µg kg-1), four levels of Ca (0.20% less than a 2:1 ratio of Ca to NPP; 2:1 ratio of Ca to NPP; 0.20% Ca greater than a 2:1 ratio of Ca to NPP; 0.40% Ca greater than a 2:1 ratio of Ca to NPP) and four levels of NPP (0.35, 0.40, 0.45 and 0.50%) for a total of 64 treatments. The primary basal diet was supplemented with a complete vitamin mix containing 5500 IU of cholecalciferol. Each diet was fed to six replicates per treatment; each pen having 6 birds. At 18 d birds were weighed, feed consumption determined and all birds killed for bone measurements. Toes from all birds within a pen were removed and ashed. Tibiae from both legs were removed and scored for incidence and severity of tibial dyschondroplasia and for incidence of Ca or P rickets. Ca: NPP ratios and Ca levels similar or higher than NRC (1994) recommendations appear necessary for adequate bird performance. Phy supplementation improved FCR, whereas the addition of 25-OH to diets already containing 5500 IU kg-1 of cholecalciferol had a negative effect on FCR due to a possible hypercalcemia condition. Bone development was improved by increasing NPP and Ca levels. Moreover, supplementation with 25-OH was effective in reducing leg abnormalities. Addition of 25-OH helped to relieve leg problems when suboptimal Ca levels were supplied while Phy supplementation was effective for this purpose when high Ca levels were given. These additives could be seen as a strategy to alleviate problems with suboptimal Ca: NPP ratios.